Human Resource Management Model in Bureaucracy in Indonesia - Butar, Immer H.P. Butar; Damayanti, Imma; Suharyo G, Brantas; Saragih, Herlina Juni Risma (Yayasan Azka Hafidz Maulana, 2024)
This research examines the development of a public sector human resource management (HRM) model that is relevant to the good governance paradigm and new management approaches. Using the documentation study method, this research identifies various HRM models, namely the Michigan Model and the Harvard Model, and links them to organizational strategy, organizational culture, recruitment, selection and HR management. The research results show that the ideal HRM model in the public sector bureaucracy in Indonesia must be able to integrate elements such as commitment, quality, HR flexibility, organizational effectiveness, and individual and community welfare. The conclusion of this research is that the development of a public sector HRM model that is comprehensive and adaptive to changes in the environment and organizational needs is very necessary to support an effective and innovative bureaucracy